Hollow spherical carbon superstructure derived from covalent organic framework as well as preparation and application of hollow spherical carbon superstructure
The hollow spherical carbon superstructure COF-CHSS and P507 composite materials derived from covalent organic frameworks solve the problems of low separation efficiency and insufficient material efficacy in the prior art, and achieve efficient and highly selective Yb3+/Lu3+ separation, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202411762247.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art has problems with low separation efficiency, large waste liquid volume and low recovery when separating 177Lu. The column separation process is limited by the efficacy of the separation material, making it difficult to adapt to harsh environments.
Through the preparation of the hollow spherical carbon superstructure COF-CHSS derived from covalent organic framework, small spherical particles COF-S are obtained by using the aldehyde amine condensation reaction of PCP-CHO and TAPD-NH2, and then self-assembled at the oil-water interface and heat-treated to form a large-sized hollow spherical superstructure. The COF-CHSS@P507 composite material is formed by combining P507 functional molecules to improve the separation efficiency and selectivity of 177Lu.
The efficient separation of Yb3+/Lu3+ is achieved, with significant selective retention ability, and can be efficiently separated even under harsh conditions with a mass ratio of 105:1, with the separation factor reaching 106.1, and the material exhibits excellent stability during recycling.
Smart Images

Figure CN119637843A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chromatographic stationary phase materials, and in particular relates to a hollow spherical carbon superstructure derived from a covalent organic framework and a preparation method and application thereof. Background Art
[0002] Radiopharmaceuticals based on radionuclide labeling are an important pillar of molecular imaging and precision medicine, providing innovative methods for tumor diagnosis and treatment, myocardial imaging and neurodegenerative diseases. 177 Lu has attracted much attention due to its suitable γ-photon and β-particle emission and low radiotoxicity, becoming a key nuclide for clinical targeted radiotherapy and driving the demand for its large-scale production. However, due to the contraction of lanthanide elements, Yb 3+ He Lu 3+ The physical and chemical properties of the 4 ~10 5 :1), which poses a huge challenge to effective separation. Although radiochemical separation methods such as ion exchange chromatography, solvent extraction and electrochemical technology have made progress in recent years, problems such as low separation efficiency, large amount of waste liquid and low recovery rate still exist, which hinders the development of carrier-free 177 Lu(NCA 177 Lu). Extraction chromatography is a promising radiochemical separation technique with great potential due to its simple operation and excellent selectivity. Unfortunately, the current column separation process is limited by the efficiency of the separation material and is not suitable for the actual harsh environment. Therefore, it is necessary to design and develop new functional column separation materials to improve 177 The efficiency and selectivity of Lu separation are crucial for large-scale production.
[0003] As an ideal material for chromatographic stationary phase, key factors include chemical stability, particle size and shape, and rich pore structure. Porous carbon materials are known for their high specific surface area, excellent chemical stability, and tunable surface properties, which have significant advantages over traditional filling materials such as silica gel, alumina, and protein. Most importantly, coordinated control of the size and micromorphology of the matrix particles is crucial to achieving high separation efficiency. From a morphological point of view, large and uniform spherical particles can enhance the uniformity and fluidity of the chromatographic column, reduce the column pressure, and improve the separation efficiency and repeatability. Combining the targeted precursor module with pyrolytic carbonization to develop a hierarchical porous carbon superstructure with precisely designed properties is the key to obtaining pure NCA. 177 Lu's ideal approach.
[0004] Among various carbon materials, carbon superstructures formed by self-assembly or epitaxial growth of low-dimensional building blocks have attracted much attention due to their multi-scale hierarchical structures and ideal functional properties. One approach is to use superstructures of metal oxides or other low-dimensional materials as self-sacrificial templates. First, a carbon source is attached to the template interface to form a carbon layer, and then the carbon superstructure is prepared by etching away the template. Another more cost-effective strategy is to directly pyrolyze a suitable precursor with a prefabricated superstructure to achieve precise morphological control. For example, polytannic acid (PTA) rods or polyacrylonitrile nanosheets are assembled into one-dimensional ribbon-like or two-dimensional film-like superstructures, which are then converted into carbon materials with similar structures. In addition, spherical structures are well-recognized for their classic morphology and play an important role in various research fields. Breakthrough progress has also been made in the preparation of spherical carbon superstructures using various substrates. However, these reported materials often have limitations such as small size, metal contamination, and weak functional surfaces, which hinder their widespread application in column separation. It is worth noting that large-sized spherical hollow superstructures with regular and enhanced surface morphology or micro-nanostructured surfaces have advantages such as close packing and high-density accessible active sites. As pillar-based materials, they can effectively enhance the interaction between host and guest and improve the efficiency of short-range mass transfer, showing great potential. However, the synthesis of such hollow spherical carbon superstructures with high carbon conversion rate and multifunctionality remains a major challenge, and new breakthroughs and synthetic concepts are urgently needed in this field.
[0005] Covalent organic frameworks (COFs) are a class of crystalline porous organic materials with highly designable and controllable morphology. Although they show strong advantages in many applications, most COFs perform poorly in harsh environments with high acidity or strong radiation. Interestingly, COFs composed of lightweight elements such as C, H, O, and N are a potential high-quality carbon source. Carbon materials derived from COFs have high carbonization efficiency, excellent structural stability, hierarchical pore structures, and tunable functional morphologies, which have opened up new avenues for the application of COFs in various challenging environments. Unfortunately, there are still no reports on the synthesis of COF-derived carbon superstructures, especially large hollow spherical structures with enhanced surface morphology. Summary of the invention
[0006] In order to solve the limitations of existing materials such as small size, metal contamination and weak functional surface, the present invention provides a hollow spherical carbon superstructure derived from a covalent organic framework.
[0007] The hollow spherical carbon superstructure derived from the above-mentioned covalent organic framework is formed by self-assembly at the oil-water interface and heat treatment after an aldehyde-amine condensation reaction between PCP-CHO (4,12-diformyl[2.2]paracyclophane) as a building unit and a four-position linker TAPD-NH2 (N,N,N',N'-tetrakis(4-aminophenyl)-1,4-phenylenediamine) under solvothermal conditions to obtain small spherical particles COF-S.
[0008] The reaction formula for obtaining small spherical particles of COF-S by the aldehyde-amine condensation reaction is:
[0009]
[0010] The preparation method of the hollow spherical carbon superstructure derived from the covalent organic framework is shown in the schematic diagram of the synthesis. Figure 1 .
[0011] The method for preparing the hollow spherical carbon superstructure derived from the covalent organic framework comprises the following steps:
[0012] a. Ultrasonic dispersion of PCP-CHO and TAPD-NH2 in a mixed solvent, then adding acetic acid, heating the reaction until the mixture gradually turns into a transparent dissolved black-red solution, and then precipitating at 50°C for 1 hour to obtain COF-S particles;
[0013] b. After the above reaction solution is prepared into a large number of water-in-oil emulsion droplets, it is allowed to stand overnight; the solid is collected by filtration, washed with DMF and methanol respectively, and then vacuum dried overnight to obtain a hollow spherical superstructure COF-HSS;
[0014] c. COF-HSS was then pyrolyzed in an argon flow at 700-900 °C for 2 h. After cooling to room temperature, it was treated with 0.1 M HNO3 solution at 70 °C for 12 h, then washed with deionized water and methanol 2-5 times, and vacuum dried overnight to obtain a covalent organic framework-derived hollow spherical carbon superstructure COF-CHSS.
[0015] In the method for preparing the hollow spherical carbon superstructure derived from the covalent organic framework, the mixed solvent in step a is o-dichlorobenzene and n-butanol. The volume ratio of o-dichlorobenzene, n-butanol and acetic acid is 5:5:2. The concentration of acetic acid is 4-7M.
[0016] In the method for preparing the hollow spherical carbon superstructure derived from the covalent organic framework, the heating temperature in step a is 100° C. to 130° C.
[0017] In the above-mentioned method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework, the molar ratio of PCP-CHO to TAPD-NH2 in step a is 1:1 to 1.2:1.
[0018] In the method for preparing the hollow spherical carbon superstructure derived from the covalent organic framework, the vacuum drying temperature in steps b and c is 60-90°C.
[0019] In the method for preparing the hollow spherical carbon superstructure derived from the covalent organic framework, the pyrolysis in step c is performed by heating starting from 30° C. at a heating rate of 5° C. / min.
[0020] The present invention also provides the use of the hollow spherical carbon superstructure derived from the covalent organic framework in the preparation of a chromatographic stationary phase material. Preferably, the chromatographic stationary phase material is used for Yb 3+ / Lu 3+ Isolated active composite materials.
[0021] The present invention provides a novel hollow spherical carbonaceous superstructure prepared by COFs, and realizes Yb 3+ / Lu 3+ In addition, the unique mass transfer effect of this superstructure and single-stage original particles on the target ions during chromatographic column separation was effectively studied, including the synthesis of hollow spherical ultrafine particles COF-HSS by in situ assembly of uniform small spherical particles COF-S during the synthesis process, and then direct high-temperature pyrolysis to generate porous carbonaceous spherical superstructure COF-CHSS with unchanged morphology. COF-CHSS has a complete superstructure and enhanced surface morphology, as well as an unusual micro / nano surface structure, making it an excellent carrier for fixing the active molecule "2-ethylhexylphosphonic acid mono-2-ethylhexyl ester" (P507). The above method provided by the present invention prepares a series of separation 177 Lu potential active composite materials, Yb in the column separation process 3+ / Lu 3+ It has remarkable selective retention ability even at a mass ratio of 10 5 :1 can achieve efficient separation. Compared with small-sized and single-layer original spherical particles, superstructure particles with larger size and more complex spatial configuration have lower column pressure, higher separation efficiency (optimal separation factor up to 106.1) and excellent cycle stability. This performance exceeds that of traditional commercial chromatographic column materials. The present invention not only introduces a new method for constructing carbon superstructures with controllable morphology, but also provides a new method for obtaining NCA 177 Lu and the blueprint for separating lanthanide metal ions with similar physical and chemical properties provide a blueprint that highlights the potential for further developments in materials science, especially in chromatography and ion separation techniques. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1(a) Schematic diagram of the synthesis mechanism of COF-HSS and COF-CHSS. (b) SEM images of COF-S, (c) COF-HSS and (d) COF-CHSS. (e) TEM image of COF-CHSS. (f) ADF-STEM and elemental mapping image of COF-CHSS. (g) EDS spectrum and elemental content analysis of COF-CHSS.
[0023] Figure 2 Characterization of COF-HSS and COF-CHSS: (a) PXRD pattern; (b) Fourier transform infrared spectrum; (c) Raman spectrum; (d) N2 adsorption-desorption isotherm at 77K.
[0024] Figure 3 (a) Schematic diagram of the synthesis of COF-CHSS@P507. Characterization of COF-CHSS@P507-25%: (b) EDS spectrum; (c) FT-IR spectrum; (d) TGA curve.
[0025] Figure 4 COF-CHSS@P507-25% for Yb 3+ or Lu 3+ Adsorption behavior and mechanism: (a) Adsorption kinetics (C0(Yb)=C0(Lu)=20.0mg L -1 , V = 9.0 mL, m = 4.5 mg, pH = 5); (b) Adsorption isotherm (V = 9.0 mL, m = 4.5 mg, pH = 5, t = 24 h); (c) Effect of HNO3 concentration (C0(Yb) = C0(Lu) = 20.0 mg L -1 , V = 9.0 mL, m = 4.5 mg, t = 24 h); (d) dynamic column breakthrough (C0(Yb) = C0(Lu) = 100.0 mg L -1 , pH = 5); (e) XPS full spectrum before and after adsorption; (f) XPS high-resolution spectrum of O1s before and after adsorption; (g) P507 and Yb 3+ or Lu 3+ DFT calculation of the binding energy of .
[0026] Figure 5 Separation of Yb 3+ / Lu 3+Dynamic elution curves of (inner diameter = 0.3 cm, mYb = mLu = 10.0 μg, gray and white areas indicate that the eluent is 0.1 M HNO3 and 1.5 M HNO3 solution, respectively): (a) Effect of different masses of P507 on column separation (h = 7.5 cm); (b) Effect of elution of COF-CHSS@P507-25% column with 1.0, 1.5 and 2.0 M HNO3, respectively (h = 7.5 cm); (c) COF-CHSS@P507-25% column with heights of 5.0, 7.5 and 10.0 cm, respectively; (d) Effect of carbonization temperature of column material (h = 7.5 cm, P507 = 25%); (e) Reuse-recycling cycle of COF-CHSS@P507-25% column (h = 7.5 cm); (f) Simulated target solution (Yb 3+ / 177 Lu 3+ =105 / 1) concentration on the COF-CHSS@P507-25% packing column (h=7.5cm).
[0027] Figure 6 (ab) SEM images of COF-CHSS@P507 and CCSM-SiO2, respectively; (c) Particle size and flow rate of different chromatographic column materials; (d) Separation of Yb by columns with different material fillers 3+ / Lu 3+ Dynamic elution curve of (inner diameter = 0.3 cm, height = 7.5 cm, mYb = mLu = 10.0 μg, gray and white areas indicate that the eluent is 0.1 M HNO3 and 1.5 M HNO3 solution, respectively); (e) Effect of different materials on the separation of Yb 3+ / Lu 3+ Schematic diagram of the impact. DETAILED DESCRIPTION
[0028] Example 1 Preparation and Characterization of Covalent Organic Framework-Derived Hollow Spherical Carbon Superstructure COF-CHSS
[0029] PCP-CHO (9.9 mg, 0.0375 mmol) and TAPD (8.85 mg, 0.0187 mmol) were placed in a 15 mL pressure tube, and then 1,2-dichlorobenzene / n-butanol (1:1 v / v, 2 mL) was added and ultrasonicated for 10 min to make it uniformly dispersed. Subsequently, 0.4 mL of 6 M acetic acid was added and the tube was sealed under nitrogen purge conditions. The container was heated to 120 ° C until the mixture gradually turned into a transparent dissolved black-red solution, and then precipitated at 50 ° C for 1 hour to obtain COF-S. Then 200 uL of the solution was absorbed by a pipette and then squeezed out to generate a large number of water-in-oil emulsion droplets. Next, the product was allowed to stand at room temperature overnight to assemble into spherical superparticles. The resulting solid was collected by filtration and washed with DMF and methanol, respectively. Finally, it was dried under vacuum at 80 ° C overnight to obtain COF-HSS powder. 0.5 g of the prepared COF-HSS was heated from 30 °C to 900 °C at a heating rate of 5 °C / min for 2 h. After cooling to room temperature, it was treated with 0.1 M HNO3 solution at 70 °C for 12 h to remove impurities. Then, it was washed with deionized water and methanol several times and dried under vacuum at 80 °C overnight to obtain 0.256 g of the final product COF-CHSS (yield: 51.3%). The preparation process is as follows Figure 1 As shown in a.
[0030] Figure 1 The scanning electron microscope (SEM) images in b and 1c reveal the unique properties of the monolayer original material COF-S and the upper self-assembled superstructure product COF-HSS. The monodispersed COF-S particles are uniformly distributed between 500 and 600 nanometers, while the upper structure product COF-HSS presents a hollow sphere morphology with a size mainly distributed around 7 to 10 microns. Impressively, during the transformation of COF-HSS to COF-CHSS ( Figure 1 d), not only the macroscopic large-scale spherical structure of COF-HSS is well maintained, but also the surface groove morphology formed by the accumulation of COF-S spheres is clearly visible. In addition, the increase in the number of carbon defects and micropores caused by the N pyrolysis process further enhances the micro-nanostructural characteristics of the surface, exposing more active sites that can interact with guest molecules. Figure 1 As shown in Figure 5, we used transmission electron microscopy (TEM) to study the details of the hollow structure of the COF-CHSS cavity. Its outer shell is composed of a single layer of COF-CS with a total diameter of about 7.8 μm and an inner cavity diameter of about 6.9 μm. Annular dark field scanning TEM (ADF-STEM) and corresponding energy dispersive spectroscopy (EDS) analysis further confirmed the structure and element distribution of COF-CHSS ( Figure 1 f and 1g). The carbon content is as high as 96.9%, indicating that COF-HSS has an extremely high carbon conversion rate advantage as a carbon source.
[0031] Powder X-ray diffraction (PXRD) patterns confirmed the crystalline nature of COF-HSS ( Figure 2 a). In order to reveal its intrinsic microstructure more clearly, the COF-HSS obtained under solvent heating condition B (m-xylene / dioxane) has higher crystallinity than that under condition A (o-dichlorobenzene / n-butanol), which is consistent with the simulated XRD of the two-dimensional AA stacking product. However, under pyrolysis conditions, the structure of COF-CHSS is partially destroyed, resulting in an increased degree of amorphism. Fourier transform infrared spectroscopy (FT-IR) is used to determine the chemical composition of the imine chain in COF-HSS and the carbon structure of COF-CHSS ( Figure 2 b) In addition, Raman spectroscopy also confirmed the successful conversion of carbon materials. Figure 2 c, located at 1360 and 1605 cm - The two peaks of 1 correspond to the D band and the G band. The D band originates from the stretching vibration of the CC bond, which corresponds to the structural defects in the carbon material; while the G band originates from the sp 2 The stretching vibration of hybrid carbon atoms and π electrons reflects the integrity of the material lattice. The ID / IG value of COF-CHSS is about 0.94, indicating that the carbon material has a short-range ordered graphite structure. The BET specific surface area and porosity of COF-HSS are 56 m 2 / g and 0.14cm 3 / g. Through thermal carbon conversion ( Figure 2 d), significantly improving the stability and specific surface area of the material (up to 729.5m 2 / g and 0.34cm 3 / g) while maintaining its main morphological features. This transformation actively improves the performance of the material in harsh environments. Compared with the pore size of 2.3nm in COF-HSS, a large number of additional micropores (0.8-1.5nm) were observed in the pore size distribution curve of COF-CHSS. This can be attributed to the structural defects caused by the pyrolysis of unreacted groups and nitrogen sites, as well as the inherent narrow pores of carbon materials. Various characterization methods confirmed that COF-HSS was successfully converted into COF-CHSS while retaining its inherent morphology. The resulting structural defects and micropores significantly enhanced its internal pores and surface micro-nanostructure characteristics. These features are expected to provide a wide range of active sites for functional components.
[0032] Example 2 Preparation and characterization of COF-CHSS@P507 composite material
[0033] The preparation and reconstruction of solid-liquid composites by bringing functional liquids into porous matrices allows for fine screening and controllable transport of target ions / molecules. 2-Ethylhexylphosphonic acid mono-2-ethylhexyl ester (P507) is an active functional molecule with different affinities for lanthanides. COF-CHSS has strong surface structural advantages and adsorption capacity, which can produce a closer interaction and adhesion with P507, thus deriving solid-liquid composites with stronger mechanical integrity and ideal dynamic interface behavior.
[0034] exist Figure 3 In a, a series of COF-CHSS@P507 composite materials with different P507 contents were prepared by uniformly confining P507 on COF-CHSS in dichloromethane. The specific steps are as follows: the prepared COF-CHSS was placed in a 50mL round-bottom flask, and a dichloromethane solution containing different amounts of P507 was added. Ultrasonic treatment was performed for 30 minutes, and the mixture was stirred at room temperature for 3 hours. After removing the dichloromethane, the obtained powder was dried at 80°C overnight to obtain COF-CHSS@P507-n with different P507 mass fractions (n=15%, 25% and 35%).
[0035] The grooves and micropores on the surface of COF-CHSS microspheres can serve as a strong anchor to hold P507 and prevent the liquid from falling off. Taking COF-CHSS@P507-25% with a P507 content of 25wt% as an example, various characterization results show that P507 can be well loaded on COF-CHSS.
[0036] SEM and graphics images ( Figure 3 b) indicates that P507 is evenly distributed on the surface of the microspheres and in the surface pores. In addition, the large particle size and uniform self-supporting morphology of COF-CHSS not only avoid high column pressure during dynamic separation, but also provide a clear internal space for guest molecules to move, increasing its theoretical plate number. The Fourier transform infrared spectrum of COF-CHSS@P507-25% shows several characteristic peaks: CH stretching vibration at 2860-2960cm -1 At 1195 cm, P=O stretching vibration -1 The P-OH bending vibration is at 1035 cm -1 At 973cm, POC stretch vibration -1 Department Figure 3 c). From the thermogravimetric analysis (TGA) curve ( Figure 3d) It can be seen that COF-CHSS has no mass loss at temperatures up to 900 °C, indicating its excellent thermal stability. In contrast, COF-CHSS@P507-25% exhibited a significant weight loss before 500 °C, which is attributed to the thermal degradation of the small molecule P507. The actual mass loss is about 27%, which is consistent with the theoretical value (25%).
[0037] Example 3 Separation of Yb from COF-CHSS@P507 composite material 3+ / Lu 3+ Conditional screening experiment
[0038] 1) Static separation experiment
[0039] Static adsorption experimental steps: 4.5 mg of adsorbent (COF-CHSS@P507-25% composite material) and 9.0 mL of Yb 3+ or Lu 3+ Aqueous solutions of different ions or acid concentrations were mixed and then shaken at 150 rpm for a specific time. Subsequently, all samples were filtered with a 0.22 μm nylon membrane filter. Finally, the Yb content in the filtrate was determined by ICP-OES. 3+ or Lu 3+ concentration.
[0040] Static batch adsorption experiments of single Yb or Lu showed that COF-CHSS@P507 composites have the ability to separate Yb 3+ / Lu 3 + potential. Figure 4 As shown in a, under the conditions of initial concentration C0 = 20 ppm and pH = 5, COF-CHSS@P507-25% rapidly captured Yb in the first 2 hours. 3+ or Lu 3+ , and the adsorption equilibrium was basically reached within 10 hours. Figure 4 The adsorption thermodynamic experiment of b also clearly reflects the adsorption selectivity of the material. COF-CHSS@P507-25% obviously has a stronger binding affinity for Lu. Figure 4 As shown in c, the adsorption capacity of COF-CHSS@P507-25% for the two lanthanides decreases with the increase of solution acidity, which indicates that highly acidic solutions can be used as potential eluents. 3+ / Lu 3+ Column breakthrough experiments performed with mixed feed solutions provided more practical insights into ion competition and interaction, demonstrating the competitive adsorption behavior of Yb and Lu on COF-CHSS@P507-25% under realistic conditions. Figure 4 d, when using Yb with C0 = 100ppm and pH = 53+ / Lu 3+ When the mixed feed solution was subjected to column breakthrough experiments, excellent purification was observed in the first 40 mL of feed. 3+ With Yb 3+ The separation difference is small, Lu 3+ Only in Yb 3+ Then it flows out slightly until the adsorption equilibrium is reached.
[0041] Further exploration of COF-CHSS@P507 for separation of Yb 3+ / Lu 3+ The researchers conducted X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) analysis to investigate the mechanism of COF-CHSS@P507-25%. Compared with the full XPS spectrum of COF-CHSS@P507-25%, the materials after adsorption of Yb or Lu showed the corresponding characteristic peaks ( Figure 4 e). The high-resolution spectra of O 1s and P 2p also show significant differences ( Figure 4 f). In view of the inherent carbon matrix, all XPS spectra were peak corrected using unsaturated carbon (284.1 eV). The O1s XPS high-resolution spectrum of COF-CHSS@P507 was split into two distinct characteristic peaks at 532.34 eV and 530.72 eV, corresponding to PO / CO and P=O / C=O, respectively. 3+ or Lu 3+ After that, the characteristic peaks of O 1s and P 2p both moved to lower binding energies, indicating that the phosphorus oxygen group is the main factor in the adsorption of metal ions. In addition, in order to reveal the intrinsic driving force behind the adsorption capacity, DFT was also used to calculate the adsorption of P507 and Yb 3+ / Lu 3+ The adsorption binding energy of Figure 4 g shows that the molecular distance between P507 and Lu(NO3)3 is smaller than that between Yb(NO3)3. The binding energy is also higher, about 7.7 kcal / mol, which indicates that P507 has a preferential affinity for Lu. Both experimental and theoretical calculations confirm that the prepared COF-CHSS@P507 has a preferential affinity for Yb 3+ / Lu 3+ Have significantly different affinities.
[0042] Although COF-CHSS@P507 has a strong adsorption capacity for Yb 3+ / Lu 3+The selectivity is weak, but the continuous mass transfer process of the dynamic interface can accelerate the interaction between ions and the adsorbent, and improve the separation efficiency through repeated adsorption and desorption processes during the chromatographic column separation process. Therefore, we loaded COF-CHSS@P507 with an ideal structure into the chromatographic column to further study Yb 3+ / Lu 3+ (mass ratio 1:1) dynamic separation.
[0043] 2) Dynamic separation experiment
[0044] Dynamic separation experimental steps: Use a glass chromatographic column (H = 10.0cm, ID = 0.3cm) to dynamically separate Yb 3+ / Lu 3 + . The upper and lower ends of the adsorbent (COF-CHSS@P507 composite material) are filled with glass fibers to prevent leakage of the glass fibers. The dry adsorbent placed in the tower must be gradually filled and continuously compacted. The upper end of the column is connected to the solution reservoir through a silicone tube, and the lower end is connected to a pump-driven collection device. In order to obtain the best chromatographic column performance, the chromatographic column needs to be immersed in dilute nitric acid before subsequent experiments. The simulated target solution (PH=5, HNO3) is Yb 3+ / Lu 3+ The mass ratio of Yb is 1:1, and the total mass of metal cations is 20.0 μg. The simulated target solution is added to the column through the reservoir, and it is first rinsed with 5.0 mL of 0.1 M HNO3 to ensure that Yb 3+ He Lu 3+ All of it flows into the column. Then Yb is eluted with 1.0-2.0M HNO3 3+ He Lu 3+ 1.0 mL of the eluate was collected and the Yb 3+ He Lu 3+ The concentration of Lu is calculated according to the following formula 3+ Recovery (R) and decontamination factor (DF):
[0045]
[0046] in and Q i are the contents of metal ion i in the initial sample and the sample after separation, respectively.
[0047] like Figure 5 As shown in a, we first studied the effects of COF-CHSS@P507 with different P507 loadings on Yb 3+ / Lu 3+To our surprise, COF-CHSS@P507 achieved an impressively high separation efficiency during column separation. 3+ / Lu 3+ There is a small amount of overlap in the elution curves, which indicates that P507 can enhance the adsorption capacity of metal ions. However, overloading of P507 will greatly reduce its mass transfer rate, resulting in a wider elution peak and lower separation efficiency. In fact, the tailing effect also leads to a decrease in the recovery rate RLu (%) and the decontamination factor (DF). Therefore, in this study, the loading amount of P507 was set to 25% to achieve the best separation efficiency. Figure 5 The separation curve in b shows that the acidity of the eluent has a great influence on the separation performance. Using 1.0M HNO3 can make Yb 3+ He Lu 3+ The decontamination factor (DF) of Lu 3+ The leaching volume reached 23 mL, and the overall separation efficiency was not ideal. The results showed that 1.5 M HNO3 could significantly reduce the leaching volume to 5 mL while maintaining a high decontamination factor (DF) of 106.1. However, under 2.0 M HNO3 conditions, the elution curves were severely overlapped and effective separation could not be achieved.
[0048] 3) Effect of column length on separation efficiency
[0049] Longer columns can provide more theoretical plates and total equilibrium adsorption capacity, thus improving separation efficiency. Therefore, we selected several column height gradients (5.0 cm, 7.5 cm, and 10.0 cm) to study the effect of column length on separation performance.
[0050] like Figure 5 c shows that consistent separation patterns were observed under different column lengths and elution acidity conditions. 3+ He Lu 3+ The overlapping area of the elution curves gradually decreases and the decontamination factor (DF) increases. However, this also leads to a decrease in flow rate and an increase in elution volume. In summary, the optimal column height is determined to be 7.5 cm.
[0051] 4) Effect of COF-CHSS prepared at different pyrolysis temperatures on separation performance
[0052] Different carbonization temperatures have a significant effect on the separation performance, such as Figure 5 As shown in Figure d, the elution peak of COF-CHSS pyrolyzed at 700 °C is broader, which increases the elution volume and separation time cost. However, the separation effect of COF-CHSS pyrolyzed at 900 °C is better.
[0053] Taking the above factors into consideration, the optimal separation conditions determined by the present invention are as follows: carbonization temperature 900°C, P507 loading 25% (COF-CHSS@P507-25%), column height 7.5 cm, and 1.5 M HNO3 elution.
[0054] Example 4 Stability of COF-CHSS@P507
[0055] Separation conditions: carbonization temperature 900℃, P507 loading 25% (COF-CHSS@P507-25%), column height 7.5cm, 1.5M HNO3 elution. The column showed excellent cycle stability, and the decontamination factor (DF) remained above 80 after three cycles ( Figure 5 e and Table 1).
[0056] Table 1 Separation of Yb by COF-CHSS@P507-25% Packing Column 3+ / Lu 3+ The reusability test results
[0057] cycle <![CDATA[Volume Lu (mL)]]> <![CDATA[Recovery rate Lu (%)]]> Decontamination Factor 1 15~20 97.1 106.1 2 16~22 95.5 82.4 3 16~22 94.8 89.4
[0058] In Table 1: mYb = mLu = 10 μg, column height h = 7.5 cm, eluent C HNO3 =1.5M, column diameter = 3mm, P507 loading = 25wt%.
[0059] Example 5 Separation experiment with different total amounts
[0060] The present invention simulates the composition of the actual target solution and conducts a tracer experiment related to the actual radioactive nucleus 177Lu. Separation conditions: carbonization temperature 900°C, P507 loading 25% (COF-CHSS@P507-25%), column height 7.5cm, 1.5MHNO3 elution.
[0061] In Yb / 177 Separation experiments with different total amounts were conducted under the harsh conditions of Lu mass ratio of 105:1. Figure 5 f, although the masses are very different, Yb 3+ / Lu 3+The elution profiles maintained similar retention volumes and peak positions. Even when the Yb content in the simulated target solution was increased from 10 μg to 50 μg, the decontamination factor (DF) remained above 20 (Table 2). However, when the Yb content was increased to 100 μg, the capacity of the column decreased significantly, resulting in a wider elution profile and ultimately reduced resolution. The main reason for the decreased separation effect is mass overloading, which occurs when the sample concentration is too high relative to the ability of the column to retain the analyte molecules. As a result, the stationary phase near the peak band becomes saturated, resulting in peak tailing and reduced column efficiency. Using a larger capacity column can alleviate this problem.
[0062] Table 2 Yb concentration of COF-CHSS@P507-25% packed column for simulated target solution 3+ / 177 Lu 3+ Separation Impact
[0063] <![CDATA[Yb 3+ Injection volume (μg)]]> <![CDATA[Volume Lu (mL)]]> <![CDATA[Recovery rate Lu (%)]]> Decontamination Factor 10.0 16~25 96.31 35.2 50.0 17~27 93.1 20.8 100.0 13~30 89.2 1.8
[0064] Example 6 Effect of the Microstructure and Physical Properties of Carbon Superstructures on Yb / Lu Separation Performance
[0065] The present invention selected COF-CS, COF-CHSS and CCSM-SiO2, which have obvious differences in morphology and structure, for comparative study. Among them, COF-CS is prepared by high-temperature pyrolysis of original spherical particles (COF-S), with a smooth surface and a size distribution of 500-600nm in the submicron level; while the upper assembly product COF-CHSS is a large-sized (7-10μm) hollow spherical superstructure with prominent surface morphology, obvious grooves and micro-nanostructures. In addition, CCSM-SiO2 is a commercial column separation material, composed of inorganic spherical silica particles of larger size (50-80μm), with a smooth surface ( Figure 6 a, 6b). In fact, the microstructure of the host (including morphology, size and surface topological features) as well as the flow rate are crucial to the chromatographic separation performance, as these factors can significantly affect the dynamic interactions and partitioning behavior between host and guest molecules.
[0066] A series of Yb 3+ / Lu 3+ Separation experiment. Figure 6 As shown in Figure c, the elution flow rates of COF-CS, COF-CHSS and CCSM-SiO2 are approximately 28 min / mL, 12.5 min / mL and 1.5 min / mL, respectively. This is in line with expectations, that is, the increase in the size of spherical particles can significantly reduce the column pressure, thereby effectively reducing the time cost. However, the separation performance of different materials shows a diversified trend. Figure 6d shows that COF-CS and COF-CHSS materials have excellent separation performance, while CCSM-SiO2 with the largest particle size and the fastest flow rate has excellent separation performance for Yb 3+ / Lu 3+ These experimental results show that the microstructure of the material and the flow rate play a crucial role in chromatographic separation. Figure 6 As shown in Figure 5, COF-S has a large mass transfer resistance due to its small particle size, smooth surface, and relatively few adsorption sites, resulting in a large elution volume and relatively poor separation efficiency. On the other hand, CCSM-SiO2, which is commonly used in industry, cannot fully achieve separation due to its large particles and smooth surface. In addition, this also reduces the number of effective active sites, and the excessively high flow rate leads to insufficient contact time between the solute and the adsorbent. It is worth noting that within the appropriate flow rate range, COF-CHSS with a complex superstructure has the best separation effect. The complex micro-nanostructure on its surface and the hollow structure inside increase its potential theoretical plate number and provide more active sites. At moderate flow rates, the balance between the main phase and the mobile phase on the dynamic interface is improved, promoting surface turbulence, thereby improving the material transfer efficiency and promoting effective separation. Another key factor in the superior separation performance of COF-CHSS is its hollow internal structure. Compared with a solid structure, it has a lower density and higher porosity, which reduces material and time costs. In addition, the internal hollow voids can absorb or load more functional molecules, allowing the material to participate in the separation process, thereby significantly improving the separation efficiency.
[0067] The present invention provides a hollow spherical carbon superstructure with enhanced surface morphology, which is formed by self-assembly of basic spherical COF particles at the oil-water interface and then heat-treated. During the pyrolysis process, it not only maintains a good inherent morphology, but also its stability and pore structure are significantly improved. The enhanced surface structural characteristics enable it to effectively carry the functional molecule P507, and a series of COF-CHSS@P507 composite materials are constructed to obtain NCA 177Lu. 3+ / Lu 3+ The static adsorption capacity and mechanism of COF-CHSS@P507 were studied in depth. Importantly, based on a large number of simulated separation experiments and radioactive tracer methods, the dynamic interface boundary separation process of COF-CHSS@P507 column was established. Under the condition of mass ratio of 105:1, a high separation performance with a decontamination factor (DF) greater than 20 was achieved, which is much higher than that of traditional commercial materials. In addition, the present invention also effectively investigated the separation effect of superstructure and original particles on the chromatographic column. The microstructure and flow rate of the material play a vital role in dynamic separation. The present invention not only emphasizes the Yb 3+ / Lu 3+This not only effectively separates lanthanides and actinides, but also expands the study of morphology-controllable carbon superstructures, providing a powerful framework for understanding structure-property relationships and paving the way for the development of advanced separation materials.
Claims
1. A hollow spherical carbon superstructure derived from a covalent organic framework, characterized by: The hollow spherical carbon superstructure derived from the covalent organic framework is formed by heat treatment after self-assembly at the oil-water interface through an aldehyde-amine condensation reaction between 4,12-diformyl[2.2]paracyclophane as a building unit and a four-position linker N,N,N',N'-tetrakis(4-aminophenyl)-1,4-phenylenediamine to obtain small spherical particles COF-S.
2. The covalent organic framework-derived hollow spherical carbon superstructure according to claim 1, characterized in that: The preparation method comprises the following steps: a. Ultrasonic dispersion of 4,12-diformyl[2.2]paracyclophane and N,N,N',N'-tetrakis(4-aminophenyl)-1,4-phenylenediamine in a mixed solvent, adding acetic acid, heating the mixture until it gradually turns into a transparent dissolved black-red solution, and then precipitating at 50°C for 1 hour to obtain COF-S particles; b. After the above reaction solution is prepared into a large number of water-in-oil emulsion droplets, it is allowed to stand overnight; the solid is collected by filtration, washed with DMF and methanol respectively, and then vacuum dried overnight to obtain a hollow spherical superstructure COF-HSS; c. COF-HSS was then pyrolyzed in an argon flow at 700-900 °C for 2 h. After cooling to room temperature, it was treated with 0.1 M HNO3 solution at 70 °C for 12 h, then washed with deionized water and methanol 2-5 times, and vacuum dried overnight to obtain a covalent organic framework-derived hollow spherical carbon superstructure COF-CHSS.
3. The method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework according to claim 2, characterized in that: The mixed solvent in step a is o-dichlorobenzene and n-butanol; the volume ratio of o-dichlorobenzene, n-butanol and acetic acid is 5:5:2; and the concentration of acetic acid is 4-7M.
4. The method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework according to claim 2, characterized in that: The heating temperature in step a is 100°C to 130°C.
5. The method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework according to claim 2, characterized in that: The molar ratio of the 4,12-diformyl[2.2]paracyclophane to N,N,N',N'-tetrakis(4-aminophenyl)-1,4-phenylenediamine in step a is 1:1 to 1.2:
1.
6. The method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework according to claim 2, characterized in that: The vacuum drying temperature in steps b and c is 60-90°C.
7. The method for preparing a hollow spherical carbon superstructure derived from a covalent organic framework according to claim 2, characterized in that: The pyrolysis in step c is carried out by heating from 30°C at a heating rate of 5°C / min.
8. Use of the hollow spherical carbon superstructure derived from a covalent organic framework according to any one of claims 1 to 7 in the preparation of chromatographic stationary phase materials.
9. The use according to claim 8, characterized in that: The chromatographic stationary phase material is used for Yb 3+ / Lu 3+ Isolated active composite materials.
Citation Information
Patent Citations
Synthesis method of azulene-based two-dimensional covalent organic framework and application of azulene-based two-dimensional covalent organic framework in electrochemical nitrogen dioxide sensor
CN112851895A
Covalent organic framework derived carbon-based material based on Co < 2 + > anchoring, preparation method and application of carbon-based material in electro-catalysis aspect
CN116344847A
COF-derived functionalized porous carbon microsphere solid-phase extractant as well as preparation method and application thereof
CN117680100A
Reversible soluble covalent organic network and'cracking-remodeling 'preparation method thereof
CN118599077A
Electrocardiogram measurement patch having water-proof tape and electrocardiogram measurement apparatus including the same
KR1020250033582A